Automatización del marketing y las comunicaciones en empresas con eCommerce B2C. Estudio de caso - Clara Inés Uribe Beltrán; Daniel Fernando Sabogal Neira; Handrix García Durán (Mundo Fesc)
This article presents the main results of a research project that characterizes the use of marketing and communications automation technologies in a B2C e-commerce company, a high-growth business model in Latin America. The objectives are to determine the use of communications and online marketing automation platforms and define how digital transformation has impacted the company. The methodology applied was a case study, which included an immersion in the selected company's technological platforms related to communications and online marketing. It also included a systematic observation of the sales funnel path under automation parameters, as well as an in-depth interview with its general manager. The results show that the company is undergoing a period of fine-tuning its automation path until reaching its final adoption and maturity. In conclusion, a reflection is offered on the digital transformation of SMEs in Colombia and Latin America and the need for training in the concept of automation and in the management of specialized platforms.